Dislocation climbing mechanism for helium bubble growth in tungsten. (1st April 2018) - Xie, Hongxian; Xu, Ke; Lu, Guang-Hong; Yu, Tao; Yin, Fuxing
Abstract: Molecular dynamics simulations were used to study the growth process of a He bubble on an edge dislocation in W, and the results indicated that the growth was controlled by a dislocation climbing mechanism. Unlike the well-known loop punching mechanism, the bubble grew by punching out interstitial atoms, which were immediately absorbed into the dislocation core, causing the edge dislocation to climb. Moreover, the dislocation climbing mechanism was shown to be more energetically favorable than the loop punching mechanism for the He bubble growth. Graphical abstract: Image 1